2014
DOI: 10.1136/vr.102151
|View full text |Cite
|
Sign up to set email alerts
|

The threat of midge‐borne equine disease: investigation of Culicoides species on UK equine premises

Abstract: There are concerns that outbreaks of exotic or novel vector-borne viral diseases will increasingly occur within northern Europe and the UK in the future. African horse sickness (AHS) is a viral disease of equids that is transmitted by Culicoides and is associated with up to 95 per cent mortality. AHS has never occurred in the UK; however, it has been suggested that appropriate Culicoides species and climatic conditions are present in northern Europe to support an outbreak. No data are currently available regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…We are not sure if this is due to the coat of the pony being denser and furrier than that of the cow, thus compelling midges to burrow more deeply, with the result that they are not extracted as easily. A similarly low number of freshly blood‐fed midges was obtained recently in a study conducted in England (Robin et al when only three of >1,400 midges captured in light traps operated adjacent to stables were shown to have engorged on the horses nearby. In this instance, the problem may have been technical as the LT is not the optimal tool to use, particularly when dealing with species active during the crepuscular, and in which activity drops off sharply soon after nightfall, especially during more cooler nights that sporadically mark the early part of the season.…”
Section: Discussionsupporting
confidence: 64%
“…We are not sure if this is due to the coat of the pony being denser and furrier than that of the cow, thus compelling midges to burrow more deeply, with the result that they are not extracted as easily. A similarly low number of freshly blood‐fed midges was obtained recently in a study conducted in England (Robin et al when only three of >1,400 midges captured in light traps operated adjacent to stables were shown to have engorged on the horses nearby. In this instance, the problem may have been technical as the LT is not the optimal tool to use, particularly when dealing with species active during the crepuscular, and in which activity drops off sharply soon after nightfall, especially during more cooler nights that sporadically mark the early part of the season.…”
Section: Discussionsupporting
confidence: 64%
“…Within the UK, there have been very few studies that have carried out blood-meal analysis of Culicoides. One study confirmed that potential UK Culicoides vector species of AHSV were blood-feeding on horses, proving a direct host-vector interaction [27]. Another study found that Culicoides impunctatus Goetghebuer, 1920, a species that is generally considered to have a very minor or no role in disease transmission, had fed on cows, sheep, deer and humans in Scotland [28].…”
mentioning
confidence: 93%
“…Based on what was learned during these outbreaks, there is little doubt that within northwestern Europe, the Culicoides attacks that all breeds of husbanded livestock endure seasonally combined with the prevailing bioclimatic regime are adequately suited to sustain a future outbreak of AHS (Robin et al, 2014). On the face of it, what would appear to increase the risk is that The Netherlands, along with Belgium, share the densest horse populations in the world (Elbers et al, 2016).…”
Section: Introductionmentioning
confidence: 99%